If \[{\log _a}x,\,\,{\log _b}x,\,\,{\log _c}x\,\] are in A.P. where x\[ \ne \]1, then show that \[{c^2} = {\left( {ac} \right)^{\left( {{{\log }_a}b} \right)}}\].
Answer
Verified
408.3k+ views
Hint: Here in the given question \[{\log _a}x,\,\,{\log _b}x,\,\,{\log _c}x\,\] are in Arithmetic progression, then the middle term will be the arithmetic mean of the other two terms. The terms given in A.P are in logarithmic form so while solving the problem we apply logarithm rules such as product rule, quotient rule and power rule.
Complete step-by-step solution:
The logarithm is the inverse function to exponent. The base b logarithm of a number is the exponent that we need to raise in order to get the number.
Given \[{\log _a}x,\,\,{\log _b}x,\,\,{\log _c}x\,\] are in arithmetic progression then the common difference between the consecutive terms will be equal
\[ \Rightarrow \]\[d = \,{\log _b}x - {\log _a}x\]-----------(1)
\[ \Rightarrow d = {\log _c}x\, - {\log _b}x\]-----------(2)
Equating (1) and (2) we get
\[ \Rightarrow {\log _b}x - {\log _a}x = {\log _c}x\, - {\log _b}x\]
On rearranging the terms
\[ \Rightarrow {\log _b}x\, + {\log _b}x = {\log _c}x\, + {\log _a}x\]
\[ \Rightarrow 2{\log _b}x = {\log _a}x + {\log _c}x\]
Using change of base rule, we get
\[ \Rightarrow \]\[2\left( {\dfrac{{\log x}}{{\log b}}} \right) = \dfrac{{\log x}}{{\log a}} + \dfrac{{\log x}}{{\log c}}\]
On taking log x common on both the sides we get
\[ \Rightarrow 2\left( {\log x} \right)\left( {\dfrac{1}{{\log b}}} \right) = \log x\left( {\dfrac{1}{{\log a}} + \dfrac{1}{{\log c}}} \right)\]
Cancelling log x on both the sides the equation reduces as following
\[ \Rightarrow 2\left( {\dfrac{1}{{\log b}}} \right) = \left( {\dfrac{1}{{\log a}} + \dfrac{1}{{\log c}}} \right)\]-------(3)
On simplifying equation (3) we get
\[ \Rightarrow \dfrac{2}{{\log b}} = \dfrac{{\log c + \log a}}{{\log a\log c}}\]-------(4)
On rearranging the equation (4)
\[ \Rightarrow 2\log c = \left( {\dfrac{{\log b}}{{\log a}}} \right)\left( {\log c + \log a} \right)\,\,\,\,\]--------(5)
Using product rule \[\log m + \log n = \log mn\] in equation (5)
\[ \Rightarrow 2\log c = \left( {{{\log }_a}b} \right)\left( {\log ac} \right)\]-------(6)
Using power rule \[n\log m = \log {m^n}\] in equation (6) we get
\[ \Rightarrow \log {c^2} = \log {\left( {ac} \right)^{\left( {{{\log }_a}b} \right)}}\]-------(7)
Now cancelling log on both the sides we get
\[ \Rightarrow {c^2} = {\left( {ac} \right)^{\left( {{{\log }_a}b} \right)}}\]
Hence proved
Note: Arithmetic progression is a sequence of numbers in which each successive term is a sum of its preceding term and a fixed term. We use \[{T_n} = a + \left( {n - 1} \right)d\]to find any term \[{T_n}\] in the given arithmetic progression, where ‘a’ is the first term of the A.P, nth position of the term, d is the common difference. Similarly \[{S_n} = \dfrac{n}{2}\left( {2a + \left( {n - 1} \right)d} \right)\] is used to find the sum of n terms of the A.P.
Complete step-by-step solution:
The logarithm is the inverse function to exponent. The base b logarithm of a number is the exponent that we need to raise in order to get the number.
Given \[{\log _a}x,\,\,{\log _b}x,\,\,{\log _c}x\,\] are in arithmetic progression then the common difference between the consecutive terms will be equal
\[ \Rightarrow \]\[d = \,{\log _b}x - {\log _a}x\]-----------(1)
\[ \Rightarrow d = {\log _c}x\, - {\log _b}x\]-----------(2)
Equating (1) and (2) we get
\[ \Rightarrow {\log _b}x - {\log _a}x = {\log _c}x\, - {\log _b}x\]
On rearranging the terms
\[ \Rightarrow {\log _b}x\, + {\log _b}x = {\log _c}x\, + {\log _a}x\]
\[ \Rightarrow 2{\log _b}x = {\log _a}x + {\log _c}x\]
Using change of base rule, we get
\[ \Rightarrow \]\[2\left( {\dfrac{{\log x}}{{\log b}}} \right) = \dfrac{{\log x}}{{\log a}} + \dfrac{{\log x}}{{\log c}}\]
On taking log x common on both the sides we get
\[ \Rightarrow 2\left( {\log x} \right)\left( {\dfrac{1}{{\log b}}} \right) = \log x\left( {\dfrac{1}{{\log a}} + \dfrac{1}{{\log c}}} \right)\]
Cancelling log x on both the sides the equation reduces as following
\[ \Rightarrow 2\left( {\dfrac{1}{{\log b}}} \right) = \left( {\dfrac{1}{{\log a}} + \dfrac{1}{{\log c}}} \right)\]-------(3)
On simplifying equation (3) we get
\[ \Rightarrow \dfrac{2}{{\log b}} = \dfrac{{\log c + \log a}}{{\log a\log c}}\]-------(4)
On rearranging the equation (4)
\[ \Rightarrow 2\log c = \left( {\dfrac{{\log b}}{{\log a}}} \right)\left( {\log c + \log a} \right)\,\,\,\,\]--------(5)
Using product rule \[\log m + \log n = \log mn\] in equation (5)
\[ \Rightarrow 2\log c = \left( {{{\log }_a}b} \right)\left( {\log ac} \right)\]-------(6)
Using power rule \[n\log m = \log {m^n}\] in equation (6) we get
\[ \Rightarrow \log {c^2} = \log {\left( {ac} \right)^{\left( {{{\log }_a}b} \right)}}\]-------(7)
Now cancelling log on both the sides we get
\[ \Rightarrow {c^2} = {\left( {ac} \right)^{\left( {{{\log }_a}b} \right)}}\]
Hence proved
Note: Arithmetic progression is a sequence of numbers in which each successive term is a sum of its preceding term and a fixed term. We use \[{T_n} = a + \left( {n - 1} \right)d\]to find any term \[{T_n}\] in the given arithmetic progression, where ‘a’ is the first term of the A.P, nth position of the term, d is the common difference. Similarly \[{S_n} = \dfrac{n}{2}\left( {2a + \left( {n - 1} \right)d} \right)\] is used to find the sum of n terms of the A.P.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE